Saccharomycopsis oxydans sp. nov., a new non-fermentative member in the genus Saccharomycopsis isolated from a traditional dairy product of Iran. Issue 2 (20th November 2019) - Hajihosseinali, Mehrdad; Nasr, Shaghayegh; Amoozegar, Mohammad Ali; Yurkov, Andrey
Abstract : A total of 21 yeast isolates were recovered as part of a research project on biodiversity of yeasts in traditional dairy products in Alborz province, Iran. Standard protocols were used to carry out phenotypic, biochemical, physiological characterization and the phylogenetic analysis of combined the D1/D2 domain of the large ribosomal subunit (26S or LSU) and ITS region sequences. Five strains represented a potential new ascomycetous yeast species. Ascospore formation was not observed in these strains, and they did not ferment the examined carbon sources. Phylogenetic analysis placed these isolates in a well-supported sub-clade in the genus Saccharomycopsis . Here, we describe this novel yeast as Saccharomycopsis oxydans sp. nov.